Kepemimpinan Kristen Di Era Disrupsi Teknologi - Daniel Ronda (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2019)
Daniel Ronda, Christian Leadership in the Era of Technology Disruption. The fast development of the technology cannot be avoided, but now these fast developments are facing disruption. However, These developments have both positive and negative impact. Related to Christianity, the disruption of technology needs to be addressed properly. Therefore, this article try to gives some direction to empower the Christian leaders in this era of technological disruption. The study of this article is using literatures to analyze the nature of technology disruption, then presents some conceptual framework for  the Christian leaders on how to deal with technological disruption. The author proposes several roles of Christian leaders that need to be carried out in the surprisingly fast changing era, such as a spiritual approach where The Word of God is a must to be a guidance to this era, an educational approach because in the era of technological disruption there is a big gap between innovation of technology and readiness of people to deal with, an integrity approach in using all kind of new technology that brought moral issues, a benefit approach in facing the diversity of technology benefits, and a humanistic approach is to relate personally with other people which is more important than any kind of relatonship in using technology. Daniel Ronda, Kepemimpinan Kristen Di Era Disrupsi Teknologi. Teknologi yang terus berkembang merupakan sebuah perkembangan yang tidak dapat dihindari, tetapi saat ini perkembangan tersebut menyebabkan terjadinya disrupsi. Perkembangan tersebut dapat berdampak secara positif maupun negatif. Dalam kaitannya dengan kekristenan, disrupsi teknologi perlu disikapi. Oleh sebab itu, artikel ini memberi arah untuk memberdayakan peran pemimpin Kristen di era disrupsi teknologi ini. Kajian yang digunakan dalam artikel ini adalah literatur yang menganalisis tentang disrupsi teknologi, kemudian mengemukakan sebuah kerangka konsep peran pemimpin Kristen di era disrupsi teknologi. Penulis mengusulkan beberapa peran pemimpin Kristen yang perlu dilakukan mengahadapi era yang berubah secara mengejutkan, antara lain: melakukan pendekatan spiritual di mana firman Tuhan adalah sebuah keharusan sebagai pedoman dan penuntun menghadapi era ini, melakukan pendekatan edukatif karena di era disrupsi teknologi ada kesenjangan antara inovasi dan kesiapan manusia untuk bersaing, melakukan pendekatan integritas dalam memanfaatkan teknologi, menggunakan pendekatan azas manfaat dalam meng-hadapi disrupsi teknologi, dan melakukan pendekatan yang humanistik.